Solar thermal performance of two innovative configurations of air-vacuum layered triple glazed windows. (May 2020) - Fang, Yueping; Memon, Saim; Peng, Jingqing; Tyrer, Mark; Ming, Tingzhen
Abstract: This study reports the optimal solar thermal performance of two innovative configurations of air-vacuum layered triple glazed window or Integrated Vacuum Window (IVW). These are when the vacuum layer of IVW is facing the warm or indoor side, i.e. IVWwarm, and when the vacuum layer of IVW is facing the cold or outdoor side, i.e. IVWcold, positions at dynamic solar insolation under winter and summer EN-ISO standard ambient conditions. A theoretically and experimentally validated finite element model is employed. The results show that in winter conditions, although the U-value of IVWwarm of 0.33 Wm −2 K −1 is lower than that of IVWcold of 0.49 Wm −2 K −1, the IVWcold has a higher solar heat gain. In sunny winter conditions, IVWcold provides higher energy efficiency while in winter night, IVWwarm provides higher energy efficiency than IVWcold . The results show that in summer conditions the U-value of IVWwarm and IVWcold are 0.34 Wm −2 K −1 and 0.51 Wm −2 K −1 respectively, while IVWwarm provides lower cooling-load and higher energy-efficiency compared to IVWcold . It is concluded that setting the vacuum gap at the indoor side position provides lower cooling-load and higher energy-efficiency compared to setting the vacuum cavity at the outdoor side position in summer ambient conditions. Graphical abstract: Image 105 Highlights: Validated thermal performance of air-vacuum layered triple glazed window (IVW) is reported. Indoor/outdoor position of vacuum layer influences solar thermal performance. Influences of dynamic solar insolation on thermal performance of the IVW are analysed. In winter conditions, the U-value of IVW on warm-side, i.e. 0.33 Wm −2 K −1, is lower than cold-side, i.e. 0.49 Wm −2 K −1 .